2021
DOI: 10.1002/slct.202101801
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ruthenium‐Based Organometallic Inhibitors against Plasmodium falciparum Calcium Dependent Kinase 2 (PfCDPK2): A Combined Ensemble Docking, QM/MM and Molecular Dynamics Study

Abstract: Recent advances in the metal‐organic framework (MOF) have accelerated the discovery of novel metal‐based anticancer, antibacterial and antimalarial compounds. This is substantiated by many serendipitously discovered metals (Ru, Rh, and Ir) based inhibitors that established the importance of metal inserted into the known organic scaffold. Conversely, it is possible to design novel bioactive compounds by mimicking hypervalent carbon atoms by transition metals. This process can be facilitated by computational dru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…Additionally, apart from switch I and switch II RMSF fluctuations (Figure 2B) commonly seen in mutated KRAS systems [26,27], no significant RMSF fluctuations were observed. PCA is a powerful tool to gain knowledge on conformational changes in a structure, with many researchers now using PCA to study ligand binding induced protein conformation changes [29,30]. In line with the RMSD and RMSF profiles, the PCA results also displayed fewer correlated motions upon hit molecules binding in comparison to reference.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Additionally, apart from switch I and switch II RMSF fluctuations (Figure 2B) commonly seen in mutated KRAS systems [26,27], no significant RMSF fluctuations were observed. PCA is a powerful tool to gain knowledge on conformational changes in a structure, with many researchers now using PCA to study ligand binding induced protein conformation changes [29,30]. In line with the RMSD and RMSF profiles, the PCA results also displayed fewer correlated motions upon hit molecules binding in comparison to reference.…”
Section: Discussionmentioning
confidence: 88%
“…As expected, the resulting plot indicated that eigenvalues for the first few vectors were higher, with the most important motions in our case contained in the first, second, and third eigenvectors. Figure 7A also demonstrates that values for the first few vectors were higher for Protein-Reference as compared to Protein-Hits, indicating that the binding of Reference leads to greater conformational changes in proteins dynamics as compared to binding of Hits [29]. We generated a 2D projection plot of these components for both the Protein-Reference and Protein-Hits (Figure 7B).…”
Section: Pcamentioning
confidence: 99%
See 2 more Smart Citations
“…Three repurposing approaches are used, which can be a computational approach, an experimental approach or mixed approaches [ 25 ]. Great advances in the development of computational drugs (CDDs) have led to more advanced algorithms that play a huge role in advances in drug discovery processes [ 6 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%